Pengaruh Daya Tarik Wisata Dan Citra Destinasi Terhadap Kepuasan Wisatawan di Kawasan Kajoetangan Heritage di Kota Malang - Saputra, Agung; Puspitasari, Reny; Purwanto, Rhiza Eka (Jurnal Pariwisata Tourista, 2023)
There are fourth importance aspects for tourist attraction such as; attraction, accessibilities, amenities, ancillary. Tourist destination also have a destination image that contains three aspects, cognition, affection, and uniqueness. This research was conducted with the aim of knowing the effect of tourist attraction and destination image on tourist satisfaction in the “Kajoetangan Heritage” area in the city of Malang. The study used quantitative methods by distributing questionnaires to 100 respondents. After doing research, analysis results obtained from the researcher shows that the tourist attraction (X1) and destination image (X2) affect tourist satisfaction in the “Kajoetangan Heritage" area in the city of Malang by 66,5% while 33,5% is influenced by other factors. Destination image has a more positive effect than tourist attraction on tourist satisfaction. Tourist satisfaction that is most felt when they travel in the “Kajoetangan Heritage" area in the city of Malang is a feeling of safe and comfortable